2004
DOI: 10.1111/j.1365-2605.2004.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in couples undergoing intracytoplasmic sperm injection. A study of 370 couples and review of the literature

Abstract: SummaryIntracytoplasmic sperm injection (ICSI) is now widely acknowledged as the most effective therapeutic approach to severe male infertility or unsuccessful in vitro fertilization. Cytogenetic investigations were performed in 370 females and 335 males prior to ICSI between January 1997 and April 2003. Nine men (2.7%) and 48 women (13%) had an abnormal karyotype, 44 females having some degree of numerical sex chromosome mosaicism. A review of the literature showed the prevalence of all types of chromosomal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
0
26
1
2
Order By: Relevance
“…Evaluation of 15 similar studies from the literature including a total of 9374 cases showed 6.54% chromosomal anomaly rate (Table 3) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study 11.74% of all cases revealed chromosomal alteration including inv (9).…”
Section: Discussionmentioning
confidence: 73%
“…Evaluation of 15 similar studies from the literature including a total of 9374 cases showed 6.54% chromosomal anomaly rate (Table 3) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study 11.74% of all cases revealed chromosomal alteration including inv (9).…”
Section: Discussionmentioning
confidence: 73%
“…Chromosome analyses have been studied in large groups of infertile patients in recent years [3][4][5][11][12][13]. In some of these studies, chromosome heteromorphisms were reported to have a higher frequency than the normal population and were regarded as abnormalities [4,5,13].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome analyses have been studied in large groups of infertile patients in recent years (Cortes-gutrienez et al, 2004;Nakamura et al, 2001;Yakin et al, 2005;Morel et al, 2004;Lissitsina et al, 2006;Madon et al, 2005). In some of these studies, chromosome heteromorphisms were reported to have a higher frequency than the normal population and were regarded as abnormalities (Nakamura et al, 2001;Yakin et al, 2005;Madon et al, 2005).…”
Section: Resultsmentioning
confidence: 99%